Etika Komunikasi Islami di Media Sosial dalam Perspektif al-Qur'an dan Pengaruhnya Terhadap Keutuhan Negara - Nazaruddin; Muhammad Alfiansyah (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2021)
In the current era of advances in information technology (new media), many immoral acts in communication activities are a challenge and a threat to harmony in the life of the nation and state within the Unitary State of the Republic of Indonesia. As M. Zia Al-ayyubi emphasized that, on social media, there are many kinds of negative content that attack certain groups and individuals, such as: statements that contain provocative values, hoaxes, hate speech, racial issues, religion and between groups (SARA). This paper examines the Ethics of Islamic Communication in the Perspective of the Koran, the Urgency of Islamic Communication Ethics on Social Media in Maintaining the Integrity of the Unitary State of the Republic of Indonesia. The research used a qualitative approach with the method of study literature Alquran / Library Research by collecting verses relating to communication ethics, then the author analyzes and concludes as a solution given by the Qur’an to good Islamic communication ethics. The results of study indicate that, the Koran provides instructions on communication ethics, namely (1) Communication must be based on Truth and Patience, (2) Filtration in receiving information (Tabayyun), (3) Avoid making fun of each other over differences, (4) Communicate in a good way and language and implied values of kindness